Phytochemicals of Extract N-Hexane Leaves Bangun-Bangun (Plectranthus Amboinicus) (Lour.) Spreng and Antibacterial Activity Causes Diarrhea - Singarimbun, Nurbaiti Br.; Firmawati Zega, Defacto; Firmawati Zega, Defacto; Anjelina Simanjuntak, Helen; Purba, Hermawan; Gurning, Kasta (Asian Journal of Pharmaceutical Research and Development, 2022)
Objective: This research aims to determine the secondary metabolites contained in the n-hexane extract of P. ambionicus leaves and to determine the effective concentration as an antibacterial causing diarrhea. Methods: The research method was carried out experimentally with the stages of making simplicia, maceration, extract making, phytochemical screening, and antibacterial activity testing. Results: The results of phytochemical screening showed the presence of flavonoids, saponins, tannins, steroids/triterpenoids. The results of the antibacterial activity test showed that the n-hexane extract of P.amboinicus leaves at all concentrations (50%, 25%, 12.5%) had antibacterial activity in the strong category (10-20 mm). Conclusion: The n-hexane extract of P.amboinicus leaves has the potential as an antibacterial with a strong category.